Screening of reference genes in Callosobruchus maculatus (Coleoptera: Bruchidae) fourth-instar larvae under high-temperature and antibiotic treatments(高温及抗生素处理下四纹豆象四龄幼虫内参基因的筛选) - 耿加美(GENG Jiamei); 何云川(HE Yunchuan); 陈秋霖(CHEN Qiulin); 高扬(GAO Yang); 周瀛(ZHOU Ying); 祝增荣(ZHU Zengrong) (浙江大学学报. 农业与生命科学版)
To identify stable reference genes for Callosobruchus maculatus fourth-instar larvae under high-temperature and antibiotic treatments, four candidate reference genes (α-tubulin_1, α-tubulin_2, RpL39_1, and RpL39_2) were selected on the basis of transcriptomic data. The expression levels of these genes were measured by real-time fluorescent quantitative polymerase chain reaction (qRT-PCR) in whole-body tissues of larvae exposed to high-temperature treatment (30 ℃ control vs. 37 ℃ treatment) and in midgut tissues of larvae subjected to antibiotic treatments (10% acetic acid control vs. 0.01% ciprofloxacin＋0.01% tetracycline hydrochloride treatment) at 30 ℃ and 37 ℃. Gene stability was evaluated by ΔCT approach, NormFinder, and GeNorm, with HSP70 as a target gene for validation. The results demonstrated that RpL39_1 exhibited the highest stability across all the treatment groups, while the combination of RpL39_1 and RpL39_2 also met the normalization requirements. HSP70 expression levels showed significant differences (P＜0.05) between the high-temperature-treated group and the control group after normalization to RpL39_1 or RpL39_2. Therefore, RpL39_1 is recommended as a single reference gene for gene expression analysis in C. maculatus larvae under high-temperature and antibiotic treatments. This study provides methodological insights into the gut microbiota-mediated regulation of heat tolerance-related genes in the host. . 为筛选高温及抗生素处理下四纹豆象（Callosobruchus maculatus）四龄幼虫的稳定内参基因，本研究基于转录组数据选取α-tubulin_1、α-tubulin_2、RpL39_1和RpL39_2作为候选内参基因，通过实时荧光定量聚合酶链反应（real-time fluorescent quantitative polymerase chain reaction, qRT-PCR）检测候选内参基因在高温处理（对照组30 ℃，处理组37 ℃）四龄幼虫整虫组织及30、37 ℃抗生素处理（对照组10%乙酸，处理组0.01%环丙沙星＋0.01%盐酸四环素）四龄幼虫中肠中的表达水平。结合ΔCT法、NormFinder、GeNorm等软件评估基因稳定性，并以HSP70为靶基因验证内参基因的稳定性。结果表明，综合所有处理组分析，RpL39_1稳定性最优，与RpL39_2组合亦可满足校正需求；采用RpL39_1或RpL39_2时，高温处理组与对照组间HSP70基因表达差异显著（P＜0.05）。综上所述，推荐使用RpL39_1作为四纹豆象四龄幼虫在高温及抗生素处理实验中的单一内参基因。本研究为解析肠道共生菌调控宿主耐热性基因表达提供了方法学基础。